2015
DOI: 10.5430/irhe.v1n1p34
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Student Teacher Stress at the University of Trinidad and Tobago

Abstract: The study explored student-teachers' perceptions of the most common indicators of stress. It sought, also, to develop separate stress categories and make comparisons among them.The sample consisted of randomly selected 306 student-teachers from two campuses of the University of Trinidad and Tobago -Valsayn and Corinth. There were thirty six males and 270 females in the study. The study examined the relationship between the student-teacher stress factors as well as the predictive power of each independent facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Academic stress can be defined as the experience of the unpleasant, negative emotions, such as anger, anxiety, tension, frustration, and depression resulting from one's work as a teacher (Kyriacou, 2001;Gowrie et al, 2015). This is the definition I adopted to do this research.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Academic stress can be defined as the experience of the unpleasant, negative emotions, such as anger, anxiety, tension, frustration, and depression resulting from one's work as a teacher (Kyriacou, 2001;Gowrie et al, 2015). This is the definition I adopted to do this research.…”
Section: Introductionmentioning
confidence: 99%
“…This is the definition I adopted to do this research. Gowrie et al (2015) showed that the correlation between professional development and curriculum-related stressors. Further, curriculum, personal, professional stressors had the greatest influence on overall student-teachers stress (Gowrie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations